Analysis of Calendar Printing Defect Control Using FMEA Method at PT Grafilin Desa Putera - Kartika, Rachmah Nanda; Ahmad, Luthfiandra (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The printing industry plays a vital role in supporting various sectors such as commerce, education, and entertainment. The quality of printed products is a key factor in attracting customers and maintaining business competitiveness. PT Grafilin Desa Putera is a printing company that produces a variety of printed materials, with calendars being one of the most in-demand products recently. This study aims to identify failure modes in the calendar printing process and analyze their root causes to reduce defects. The method used is Failure Mode and Effect Analysis (FMEA), which evaluates risks based on the Risk Priority Number (RPN). The results show that the total RPN value across identified failure modes reached 910, with the highest individual RPN of 252 attributed to the issue of blanket smashing or blanket rupture. These findings serve as a foundation for developing corrective strategies to improve the quality and efficiency of the production process at PT Grafilin Desa Putera.